Nicotine is associated with smoking dependence and vascular inflammation through cotinine: A mediation analysis - Kumboyono Kumboyono; Indah N. Chomsy; Nadya N. Shalshabilla; Hidayat Sujuti; Arie Srihardyastutie; Cholid T. Tjahjono; Teuku Heriansyah; Titin A. Wihastuti (Tobacco Induced Diseases)
Introduction The main alkaloid component in cigarettes is nicotine. Cotinine, a metabolite of nicotine, is capable of causing dependence effects through endless mechanisms modulated by the ion channel nicotinic acetylcholine receptors nAChRs. Nicotine and cotinine can also cause damage to blood vessels through a chronic inflammatory process mediated by the Ligand-Tie2 Angiopoietin Receptor system. Hypoxic conditions that occur due to vascular inflammation cause a decrease in the concentration of nitric oxide (NO). This study aimed to evaluate the relationship between NO levels and cotinine through the expression of nAChRs that mediate the nicotine dependence mechanism and Tie2 (Tyrosine Kinase 2) expression.